Discovery and Biological evaluation of pyrimido[4, 5-d]pyrimidine-2, 4(1H, 3H)-dione derivatives as potent Bruton's tyrosine kinase inhibitors. Issue 15 (1st August 2019) - Diao, Yanyan; Fang, Xiaoyu; Song, Peiran; Lai, Mengzhen; Tong, Linjiang; Hao, Yongjia; Dou, Dou; Liu, Yingqiang; Ding, Jian; Zhao, Zhenjiang; Xie, Hua; Li, Honglin
Graphical abstract: Abstract: Aberrant activation of B cell receptor (BCR) signal transduction cascade contributes to the propagation and maintenance of B cell malignancies. The discovery of mall molecules with high potency and selectivity against Bruton's tyrosine kinase (BTK), a key signaling molecule in this cascade, is particularly urgent in modern treatment regimens. Herein, a series of pyrimido[4, 5-d]pyrimidine-2, 4(1H, 3H)-dione derivatives were reported as potent BTK inhibitors. Compounds17 and18 displayed strong BTK inhibitory activities in the enzymatic inhibition assay, with the IC50 values of 1.2 and 0.8 nM, respectively, which were comparable to that of ibrutinib (IC50 = 0.6 nM). Additionally, compound17 had a more selective profile over EGFR than ibrutinib. According to the putative binding poses, the molecular basis of this series of compounds with respect to potency against BTK and selectivity over EGFR was elucidated. In further experiments at cellular level, compounds17 and18 significantly inhibited the proliferation of Ramos and TMD8 cells. And they arrested 75.4% and 75.2% of TMD8 cells in G1 phase, respectively, at the concentration of 1 µM.